A composite equation of state for the modeling of sonic carbon dioxide jets in carbon capture and storage scenarios. Issue 10 (15th April 2013) - Wareing, Christopher J.; Woolley, Robert M.; Fairweather, Michael; Falle, Samuel A. E. G.
<x xml:space="preserve">Abstract</x> The development of a novel composite two‐phase method to predict the thermodynamic physical properties of carbon dioxide (CO2) above and below the triple point, applied herein in the context of Reynolds‐Averaged Navier–Stokes computational modeling has been detailed here. A number of approaches have been combined to make accurate predictions in all three phases (solid, liquid, and gas) and at all phase changes for application in the modeling of releases of CO2 at high pressure into the atmosphere. Predictions of a free release of CO2 into the atmosphere from a reservoir at a pressure of 10 MPa and a temperature of 283 K, typical of transport conditions in carbon capture and storage scenarios, is examined. A comparison of the results shows that the sonic CO2 jet that forms requires a three‐phase equation of state including the latent heat of fusion to realistically simulate its characteristics. © 2013 American Institute of Chemical Engineers AIChE J, 59: 3928–3942, 2013